USE THE TRIZ METHOD TO TEACH MECHANICAL ENGINEERING - Mansurov Muxtorjon Toxirjonovich; Toshtemirova Gulnora Ayubjanovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The systematization of teachers' knowledge in the field of pedagogy, which is to teach educators to understand the unity and contradictions of the world around them and to give concrete practical education to creative individuals who are able to solve any of their problems.